2016
DOI: 10.1080/10910344.2016.1165835
|View full text |Cite
|
Sign up to set email alerts
|

Surface crack density and recast layer thickness analysis in WEDM process through response surface methodology

Abstract: In this work, quantitative assessment of surface damage in terms of parameters like surface crack density and recast layer thickness in wire electrical discharge machining (WEDM) process has been undertaken. The effect of processing conditions on crack formation is studied using scanning electron microscope. Surface crack density and recast layer thickness analysis in terms of machining parameters such as pulse on time, pulse off time, peak current, spark gap voltage significantly deteriorate the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 33 publications
(33 reference statements)
2
30
0
2
Order By: Relevance
“…EDM with kerosene as dielectric fluid produces thinner and porous recast layer as well as finer and harder surface when compared to water emulsion. It was also reported that the white layer thickness decreases with a decrease in pulse duration (electrical energy) [152]. In addition, an EDM automatic finishing setting and the addition of powder to the dielectric fluid reduced the formation of a recast layer [11,153,154] as depicted in Figure 18.…”
Section: Formation and Influence Of Recast Layer On Edmedmentioning
confidence: 88%
“…EDM with kerosene as dielectric fluid produces thinner and porous recast layer as well as finer and harder surface when compared to water emulsion. It was also reported that the white layer thickness decreases with a decrease in pulse duration (electrical energy) [152]. In addition, an EDM automatic finishing setting and the addition of powder to the dielectric fluid reduced the formation of a recast layer [11,153,154] as depicted in Figure 18.…”
Section: Formation and Influence Of Recast Layer On Edmedmentioning
confidence: 88%
“…1b). This can be because of the reason that due to rapid heating and quenching, the local temperature increases more than the melting point of the material resulting in the formation of cracks with the development of high thermal stress exceeding the plastic deformation (Kumar et al, 2016). In this study the size and density of cracks were measured in terms of surface crack density at low and high discharge energy by using equation 1.…”
Section: Surface Structure Of Machined Samplementioning
confidence: 99%
“…Research on deficiency of surface quality in the form of micro-cracks, thermal stress, vast recast layer and improper material removal are existing [12,13]. Improper machining and loss in surface quality may lead to effect on service life of the machined component with residual stress [14][15][16][17]. To identify the influence of process parameters experiments are defined in different combinations of process parameters to predict the responses and also to optimize best process conditions [11,18,19].…”
Section: Introductionmentioning
confidence: 99%